2021
DOI: 10.3390/biom11101536
|View full text |Cite
|
Sign up to set email alerts
|

Automated Fiber Diameter and Porosity Measurements of Plasma Clots in Scanning Electron Microscopy Images

Abstract: Scanning Electron Microscopy (SEM) is a powerful, high-resolution imaging technique widely used to analyze the structure of fibrin networks. Currently, structural features, such as fiber diameter, length, density, and porosity, are mostly analyzed manually, which is tedious and may introduce user bias. A reliable, automated structural image analysis method would mitigate these drawbacks. We evaluated the performance of DiameterJ (an ImageJ plug-in) for analyzing fibrin fiber diameter by comparing automated Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Although SEM provides valuable information about clot and fibrin networks 89,90 , typical analysis is manual and tedious. Newer automated platforms are now being developed to increase accuracy and reproducibility in imaging clots 91 . Several studies have used SEM to facilitate understanding of thrombus formation, platelet adhesion and platelet properties under flow and mechanical stress 81,[92][93][94] .…”
Section: Box 1 | Pre-analytic Challenges In Platelet Investigationsmentioning
confidence: 99%
“…Although SEM provides valuable information about clot and fibrin networks 89,90 , typical analysis is manual and tedious. Newer automated platforms are now being developed to increase accuracy and reproducibility in imaging clots 91 . Several studies have used SEM to facilitate understanding of thrombus formation, platelet adhesion and platelet properties under flow and mechanical stress 81,[92][93][94] .…”
Section: Box 1 | Pre-analytic Challenges In Platelet Investigationsmentioning
confidence: 99%
“…A major drawback of the included tools is the fact that the pores are mostly measured in 2D images, while it is important to measure pores in 3D to get reliable information since pores can have different sizes in all three dimensions. Pore size and porosity as measured by DiameterJ were indeed shown to be poorly correlated with functional permeability measurements of plasma clots 8 . While pore sizes have been measured in 3D [66][67][68] , and it was shown that it is possible to work with 2D images while correcting for the missing third dimension 69 , these tools are unfortunately not publicly available.…”
Section: Discussionmentioning
confidence: 97%
“…Until recently, quantification of fiber diameters was often done manually, which is inefficient and sensitive to observer bias 8,60 . We tested eight available tools to automatically measure fiber diameter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations